Gerakan Literasi Masyarakat melalui Implementasi Pojok Baca pada Tempat Pembelajaran Al-Qur’an di Kalangan Anak Usia Dini - Khasanah, Fata Nidaul; Untari, Dhian Tyas; Zahra, Fina; Ramadhani, Bianca Salikha; Khofifah, Siti Nur; Ghozali , Daffa Khuzaimy (Jurnal Pemberdayaan Masyarakat, 2024)
Gerakan Literasi Membaca (GLM) is an activity carried out to strengthen the sensitivity of lifelong learning by utilizing all the abilities possessed by the community. The reading corner is the use of a corner of space that is used as a means to bring books closer so that people are more interested in reading. The creation of a reading corner has a wide range of benefits, namely it is expected to be able to stimulate or stimulate the community to love reading. The activity partner is the Al-Quran Learning Place (TPA) in South Tambun. The problem that exists at the partner location is the lack of special infrastructure facilities that can be used as a forum to foster a reading literacy culture, the lack of reading book materials as a basic literacy media in this is the trigger for a low reading literacy culture. The solution offered uses the room as a corner of the reading room by providing infrastructure facilities to support literacy activities and conducting training activities as an effort to share information related to the use of information technology in supporting learning activities at the landfill. As a result of the overall activities, partners felt the benefits of the proposed program and from the results of the percentage evaluation questionnaire that was achieved 100%.